Effect of STEM-PBL advanced mathematics course on engineering students’ problem-solving ability in higher vocational college - Wang, Jing; Somasundram, Piriya (Frontiers in Education, 2025)
This study explores the effect of STEM-problem based learning (STEM-PBL) advanced Mathematics on engineering students’ problem-solving ability (PSA) in higher vocational colleges. Grounded in STEM-PBL and student’s PSA framework, the study integrates mobile and digital technologies, including GeoGebra and MATLAB, into a context-rich instructional design. A quasi-experimental design was employed involving 83 students, with 42 assigned to the experimental group (EG) and 41 to the control group (CG). Quantitative data were collected through pre-test, post-test, and analyzed using SPSS. The results showed that STEM-PBL instruction significantly improved students’ PSA. These findings suggest that incorporating STEM-PBL content and digital tools into mathematics education is essential for developing basic PSA among engineering students. This study provides practical guidance for designing effective, equitable, and skill-oriented STEM courses in vocational education.